Barriers and Supports for UX/Design Leaders: from Tactical to Strategic Collaboration. (20th November 2020) - Frishberg, Nancy; Convertino, Gregorio
Abstract : The establishment of a UX Research function within the newly recognized Customer Experience organization gave rise to cases of failure and success, and developed a roadmap toward increased feedback from end‐user customers, as well as lessons in risk prevention.